Reducing anxiety and depression symptoms in pregnancy: Case report of maternal mental health from Indonesia - Sari, Dewi Nirmala; Safrudin, Safrudin; Mardeyanti, Mardeyanti; Karningsih, Karningsih; Yulfitria, Fauziah (Universitas Aisyah Pringsewu, 2023)
Mental health is neglected in antenatal care in Low- and Middle-Income Countries, whereas the prevalence of anxiety and depression symptoms in pregnant women is increasing yearly. Mindfulness is a new recommended method to prevent and reduce symptoms of anxiety and depression, but it is still rarely practised in Indonesia. This case report aimed to explore mindfulness-based interventions reducing anxiety and depression in pregnant women. The subjects of this study were two pregnant women who had symptoms of anxiety and depression. The research was conducted at the Community Health Centers from April to May 2023. The results were that mindfulness-based interventions built with husbands’ involvement can help reduce anxiety and depression symptoms in pregnancy. Mindfulness-based interventions are a practical and inexpensive program. Based on our findings, mindfulness programs should be taken into strategies to prevent mental health disorders in antenatal care. Health professionals can teach this method during pregnant women's antenatal care visits or in pregnant women's classes.